(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This review covers common gynecological disorders in adolescents, such as menstrual irregularities, dysmenorrhea, abnormal bleeding, and infections. Adolescence requires specialized care distinct from pediatric and adult gynecology, focusing on conservative treatment, patient education, and family involvement. Advances in hormonal therapy, minimally invasive diagnostics, and reproductive health education have improved outcomes. Providers must consider developmental stages, confidentiality, and cultural factors. This review offers evidence-based guidance for managing adolescent gynecological issues.